2014
DOI: 10.2134/agronj13.0367
|View full text |Cite
|
Sign up to set email alerts
|

Management of Furrow Irrigation and Nitrogen Application on Summer Maize

Abstract: The efficient use of water and N represents a primary concern to agricultural production in Northwest China. The objective of this study was to assess the impacts of irrigation and fertilization on water and N use, soil volatilized NH 3 , soil NO 3 leaching, and NO 3 transfer in soil profiles. A 2-yr field experiment was conducted to assess the separation of N fertilizer and water with alternating furrow irrigation (SNWAFI) and conventional irrigation and fertilization (CIF) in a maize (Zea mays L.) production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies, such as Jia et al (2021), found that alternate furrow irrigation (AFI), with an equivalent water volume of 150 mm, significantly increased winter wheat's N uptake efficiency (NUPE) by 8.0% compared to the flood irrigation. Han et al (2014) also demonstrated that AFI combined with separated N fertilizer applications, improved N agronomic efficiency by 36−56% in summer maize compared to conventional irrigation methods. Comparable enhancements in N use efficiency (NUE) of AFI under the same irrigation quantities were recorded with sugar beets in Turkey (Mon et al, 2016) and safflower in Iran (Shahrokhnia and Sepaskhah, 2016).…”
Section: Enhancement Of N Use Efficiency By Fi Afi and Tn At Jointingmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies, such as Jia et al (2021), found that alternate furrow irrigation (AFI), with an equivalent water volume of 150 mm, significantly increased winter wheat's N uptake efficiency (NUPE) by 8.0% compared to the flood irrigation. Han et al (2014) also demonstrated that AFI combined with separated N fertilizer applications, improved N agronomic efficiency by 36−56% in summer maize compared to conventional irrigation methods. Comparable enhancements in N use efficiency (NUE) of AFI under the same irrigation quantities were recorded with sugar beets in Turkey (Mon et al, 2016) and safflower in Iran (Shahrokhnia and Sepaskhah, 2016).…”
Section: Enhancement Of N Use Efficiency By Fi Afi and Tn At Jointingmentioning
confidence: 88%
“…Previous research demonstrated that N fertilizer topdressing can modulate soil nitrate−N accumulation, and its effects influenced by water management strategies (Zhao and Yu, 2006;Shi et al, 2012;Li et al, 2020). Han et al (2014) compared AFI and N topdressing paired to conventional irrigation and fertilization, noting that the former increased nitrate−N in the upper soil (0-60 cm) by 30−60% while reducing it in the deeper layers (60-200 cm) by 8−44% in summer maize farmland, mainly due to the enhancement of N requirement and root morphology from the optimized moisture introduced by AFI. In our investigation, TN treatments with 60 kg N ha −1 topdressing at the jointing stage consistently improved the soil nitrate−N accumulation in most soil layers at the booting and anthesis stages, regardless of the irrigation techqiue employed, although the differences waned as the wheat matured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, the maize yield and water requirement under the furrow method were reported to be 6.12 t ha −1 and 425.9 mm, respectively (Khan et al, 2015). The use of AFI enhances maize yield (9–16%) and WP (36–56%) (Han et al, 2014). AFI, at 70% soil moisture depletion, showed a saving of 65% irrigation water compared to the normal furrow method (Narayanan & Seid, 2015).…”
Section: Strategies For Water Productivity Enhancementmentioning
confidence: 99%
“…Excess application of water resulted in NO 3 -N leaching (Ju, Liu, Zhang, & Roelcke, 2004;Gheysari, Mirlatifi, Homaee, Asddi, & Hoogenboom, 2009). Furthermore, compared to conventional furrow irrigation (CI) and fertilization, separation of N fertilizer and water with alternate PRI increased NO 3 -N in the upper soil layers (0-60 cm) by 30 to 60%, while reduced that in the deeper soil layers (60-200 cm) by 13 to 33% (Han et al, 2014). Placement of N fertilizer in the ridge rather than the furrow could lower N leaching in fixed PRI or CI (Benjamin, Havis, Ahuja, & Alonso, 1994;Benjamin, Poter, Duke, & Alnoso, 1997), so did placement of N fertilizer in non-irrigated rather than irrigated furrow in fixed PRI (Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%